2018
DOI: 10.22437/ijolte.v2i1.4529
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ICT in English Language Learning: Students’ Perceptions of a State University in Jambi Province

Abstract: This research was done in order to know students' perception toward integrating ICT in English Language Learning and also to find out problem that may faced by students during the ICT integration. This research used quantitative method in order to describe students' perception toward the use of ICT in ELL. This research involved English students from a state university in Jambi province as the respondents. The data were collected by using questionnaires adapted from Chutopama (2004). The questionnaires consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…This utterance means this training gave good impact on the participants. As [7], [8], [9], [10] and [11] who researched on the perception or belief of using ICT either from the students' view or teachers' view. The results of those studies showed that the students and the teachers had a positive response toward the ICT utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This utterance means this training gave good impact on the participants. As [7], [8], [9], [10] and [11] who researched on the perception or belief of using ICT either from the students' view or teachers' view. The results of those studies showed that the students and the teachers had a positive response toward the ICT utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, [5] and [6] conducted conceptual research on the use of ICT, for instance, Edmodo and Facebook in the teaching and learning process. Second, [7], [8], [9], [10] and [11] who conducted the research on the perception or belief of using ICT either from the students' view or teachers' view. The results of those studies showed that the students and the teachers had a positive response toward ICT utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the ICT should be integrated in English language classroom in order to attract students' motivation, so they can have positive attitude in using ICT for English language learning. The ICT integration can improve students' English language skills (Oktalia et al, 2018;Zhang & Pérez-Paredes, 2019). The students also believe that utilizing ICT in the learning process makes ELL more fun.…”
Section: Discussionmentioning
confidence: 95%
“…In the Indonesian context, especially in the English Study Program of a state university in Jambi, the students believe that ICT is useful to be implemented in English language learning. They used ICT only for the presentation media in teaching and learning process in the classroom (Oktalia et al, 2018). Furthermore, the students used ICT to enrich their knowledge related to the topic given by the lecturer.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents feel that coursework, tutorials, and exams can impact their understanding (De Backer et al, 2012). It might be argued that the use of ICT can assist pupils in enhancing their English language skills (Oktalia, D., Ngadiso, & Supriyadi, 2018). In addition, they feel that using ICT into the teaching and study of ELL may make the subject more enjoyable.…”
Section: Discussionmentioning
confidence: 99%